(untitled) (Research, Society and Development, 2021)
Milk is a food widely consumed by people of all age groups, because it provides calcium and protein for the human diet. With the increase in the number of people with a deficiency of the enzyme lactase, which causes gastrointestinal disorders after the consumption of milk and its derivatives, there are several innovations that facilitate the feeding of people with intolerance. Thus, the enzyme lactase of microbial origin has been the most indicated and only authorized for use in food processes for the hydrolysis of lactose. The objective of this study was to evaluate the hydrolysis of lactose present in semi-skimmed fluid milk at intervals of 5 minutes until the final time of 60 minutes. Two different assays were performed on the activity of the β-galactosidase enzyme: a) using commercial enzyme lactase produced by Aspergillus orizae and b) using enzymatic preparation containing lactase of microbial origin (A. orizae), protease and lipase. The composition of the milk was evaluated using the Master Mini ® equipment with ultrasonic operation principle. The hydrolysis caused changes in some physical-chemical characteristics of milk, increased density, non-greasy solids, proteins, minerals and freezing point reduction. The two enzymes showed different results, since one of them provided a greater reduction than the other one, but did not reach 90%. The value found in the present study was significantly lower than expected for a product targeted to lactose intolerant individuals.